A comparative investigation of the impact of financial disclosure in conventional and Islamic banks on stock returns in selected GCC countries - Azrak, Tawfik (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
Diverse attempts have been made to analyse the impact of financial disclosure on the stock returns volatility of banking sector. In light of theoretical and empirical results available in this domain, two contradictory views have emerged. Some researchers are of the opinion that financial disclosure will enhance the banking stock returns stability since it will increase the trust between the shareholders, while others have opposite viewpoint and they argue that enhancing the financial disclosure will lead to inject more data into the market which will be misunderstood by the investors and therefore it will increase the stock return volatility. This thesis provides empirical evidence of a linear relationship between financial disclosure and stock returns volatility, which shed light on the conflicting results of previous theoretical and experimental studies. In our study, we are exploring the financial disclosure levels of Islamic and conventional banks in five Gulf Cooperation Council (GCC) countries which have dual banking system with a significant share of Islamic banking for the period of 2005 until 2015 and find which banks is more transparent to the market. Furthermore, we are studying the disclosure – stock return volatility relationship and we are exploring whether or not bank types affect this relationship and which banks have higher stock return volatility effects. Using fixed or random effect technique on panel data covering the GCC countries with dual banking system, this thesis finds and affirms that the disclosure levels in conventional banks were better than Islamic banks in GCC region during the studied period, but interestingly at the same time we find that the gap between the financial disclosure levels in these two banking system was decreased from 13.96% in 2005 to become 5.51% in 2015, and this indicate the efforts and enhancement done to improve Islamic banking system during the last few years. Additionally, the empirical finding confirms that increasing the financial disclosure level will lead to increase the stock returns volatility for both banking system in a different ratio. Analysis of the differences among Islamic and conventional banks verified that the effect of the financial disclosure will be higher for stock returns volatility of Islamic banks. These results have significant policy implications, as it suggests that policymakers should encourage the banks to have clear guidance on the required information to be disclosed on multiple criteria. Instead of recommending for injecting more information in the market, the focus should be made on the dissemination of reliable, adequate, relevant, and timely information. Furthermore, results derived in this thesis have direct implications for managers and policymakers in GCC banking system, who can use this information to design better disclosure policies to influence investors.